Law enforcement agencies: issues of terminology and system - Farion-Melnyk, Antonina; Yaremko, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2020)
The article focuses on the absence of a proper normative definition of the term «law enforcement agencies» in Ukraine. The legal analysis of the definitions concept was conducted that are enshrined in legislation and developed by domestic scientists. There was noted that mostly domestic scientists in defining the concept of ‘law enforcement agencies’ primarily focus on the authorities that form the system of law enforcement agencies as well as on the functions they perform. There was stated that in order to clear understanding of the essence concept of «law enforcement agencies» it is necessary to distinguish correctly it from such relevant concepts as «law enforcement system», «law enforcement», «state law enforcement service»,«law enforcement», «criminal justice», etc. There was admitted that the concepts of «law enforcement agencies» and «law enforcement agencies» are related as generic and species. It was grounded that the idea of referring the court to the law enforcement system contradicts the content and priority of the judiciary – the administration of justice. In the context of the study the essence of the concept of «law enforcement agencies»revealed the content and functions of these authorities. Two definitions were proposed: «law enforcement» and «law enforcement system». Law enforcement agencies are public authorities by functional criteria were aimed at the professional implementation of law enforcement activities to ensure the rule of law and order, protection of rights, freedoms and legitimate interests of individuals, rights and legitimate interests of legal entities, the interests of society and the state from unlawful encroachments. It was noted that in Ukraine law enforcement agencies often undergo certain changes related to their tasks, functions, organizational structure, powers, etc. Therefore, we do not consider it appropriate to disclose the meaning of the definition of «law enforcement system» by listing the subjects of law enforcement. «Law enforcement system» is a holistic, hierarchical, structured set of interconnected and interacting law enforcement agencies, by functional criteria aimed at the professional implementation of law enforcement in order to ensure the rule of law and order, protection of rights, freedoms and legitimate interests of individuals, rights and legitimate interests of legal entities, the interests of society and the state from unlawful encroachments.